The Design and Evaluation of Online Interactive Learning in an Undergraduate Nutrition Course - Livingstone, Katherine M.; Milte, Catherine M.; Macfarlane, Susie; Woods, Julie; Booth, Alison (Frontiers in Nutrition, 2022)
Understanding factors that promote student engagement with online learning environments is important for benchmarking and improving the quality of teaching in a digital era. This study aimed to describe the online interactive content created for delivery of an undergraduate nutrition course and to evaluate student engagement with the online interactive content. We collected online questionnaire data in 2018 and 2019 from two cohorts of students enrolled in a Deakin University undergraduate nutrition unit. Two-sample unpaired t-tests were used to examine differences in participant engagement with topic guides between static text-based and interactive topic guides. A total of 89 participants (19-56 years) were included. With the online static text-based topic guides, 64% of students reported always/usually reading static text-based topic guides most weeks and 64% perceived them as moderately/highly effective. With the online interactive topic guides, 60% of participants reported reading online interactive topic guides most weeks and 93% perceived them as moderate/highly effective. Most participants indicated the interactive topic guides were more effective than static text-based topic guides they experienced in other courses (76%). Hours dedicated to the online interactive topic guide were higher (6.4 SD 2.9 vs 1.7 SD 1.7 hours; P<0.001) as was the rating of how engaging the topic guides were (7.2 SD 1.6 vs 6.7 SD 2.5; P=0.008). These findings suggest interactive content is more engaging. However, this content may not be accessible to all students, and so familiarization and training prior to engaging in an interactive online unit may be needed.